Estudo da comunidade fitoplanctônica do reservatório Acarape do Meio com ênfase em cianobactérias - Santos Júnior, Francisco Rodrigues Pessôa dos (2014)
The water quality from a reservoir is subject to all natural and anthropogenic factors acting in its watershed . The state of Ceará since the late 80s has adopted a policy of construction of water reservation to fulfill the so-called hydric emptiness. It has been observed that the waters of these new lakes, as well as the previously constructed , is experiencing a process of deterioration, mainly caused by eutrophication. The eutrophication causes a series of changes in the water system, the most relevant being the cyanobacteria blooms. Some of these organisms may be capable of producing toxins, termed cianotoxins , which are able of causing diseases and, in extreme cases, humans and animals death. This work was performed at the Acarape do Meio reservoir, located in the municipality of Redenção - Ceará. Phytoplankton community data, with emphasis on cyanobacteria, was analyzed during the period of May 2012 to May 2013. 49 taxa distributed into 07 classes , Cyanobacteria representing 40 %, were identified. Despite the elevated number of taxa of algae, total quantity of these organisms ranged from 2.16 % (May/2012 ) to 0.34 % ( June/2012 ) while cyanobacteria were present in all samples, ranging between 97.84 % ( May/12 ) to 99.66% ( junho/12 ), quantitatively dominating the aquatic environment . The dominant species in all samples was the cyanobacterium Cylindrospermosis raciborskii, reaching an average density in April, 2012 of 1.121.328 cel.mL-1. As for the Trophic State Index, it pointed out that the reservoir was eutrophic . When the density of cyanobacteria was correlated with rainy periods and macronutrients , it showed a strong positive correlation with seasonality but a weak correlation with nitrogen and phosphorus, probably caused by the high quantities of these macronutrients present during the study period.